Antibacterial Activity of Chrysanthemum buds Crude Extract Against Cronobacter sakazakii and Its Application as a Natural Disinfectant - Chang, Yunhe; Xing, Min; Hu, Xinying; Feng, Hongxia; Wang, Yao; Guo, Bingrui; Sun, Maocheng; Ma, Lizhi; Fei, Peng (Frontiers in Microbiology, 2021)
Cronobacter sakazakii is an opportunistic food-borne pathogen that endangers the health of neonates and infants. This study aims to elucidate the antibacterial activity and mechanism of Chrysanthemum buds crude extract (CBCE) against C. sakazakii, and its application as a natural disinfectant. The antibacterial activity was evaluated by the determination of the diameter of inhibition zone (DIZ), minimum inhibitory concentration (MIC), and minimum bactericide concentration (MBC). The antibacterial mechanism was explored based on the changes of growth curve assay, intracellular ATP concentration, membrane potential, intracellular pH (pHin), content of soluble protein and nucleic acid, and cell morphology. Finally, the inactivation effects of CBCE against C. sakazakii in biofilm on stainless steel tube, tinplate, glass and polystyrene were evaluated. The results showed that the DIZ, MIC, MBC of CBCE against C. sakazakii were 14.55±0.44 14.84±0.38 mm, 10 mg/mL, and 20 mg/mL, respectively. In the process of CBCE acting on C. sakazakii, the logarithmic growth phase of the tested bacteria disappeared, as well as, the concentrations of intracellular ATP, pHin, bacterial protein and nucleic acid were reduced. Meanwhile, CBCE caused the cell membrane depolarization and leakage of cytoplasm of C. sakazakii. In addition, about 6.5 log CFU/mL of viable C. sakazakii in biofilm on stainless steel tube, tinplate, glass and polystyrene could be inactivated after treatment with 1 MIC of CBCE for 30 min at 25°C. These findings reveal the antibacterial activity and mechanism of CBCE against C. sakazakii, and provide a possibility of using natural disinfectant to kill the C. sakazakii in the production environment, packagingmaterials, and utensils.